Groningen 2021 - Diego Mideros; Kerstin Dofs (Studies in Self-Access Learning Journal, 2022)
Last year, on August 18th, the Research Network on Learner Autonomy (ReNLA) symposium entitled “Autonomy in the time of complexity in a changing world” took place as part of the online AILA Congress 2021. Together with Andy Gao, we planned the symposium carefully between 2018 and 2019 for the original 2020 congress. We were obviously disheartened when the congress had to be postponed and disappointed that we could not meet old-time friends and new faces physically as we had originally envisioned. Nonetheless, we were happy with the outcome of the online symposium and the possibility to see and interact with the presenters and attendees even if it was through a screen. Although it was particularly difficult to work around the time differences with presenters from different continents and time zones, the symposium was a fruitful ground to learn and discuss what autonomy colleagues and enthusiasts are doing to promote and further understand learner autonomy in different parts of the globe.